Infectious Pancreatic Necrosis Virus in Salmonids: Molecular Epidemiology and Host Response to Infection - Reyes-Lopez, F (John Wiley and Sons Inc, 2022)
Infectious pancreatic necrosis virus (IPNV) is one of the most pervasive pathogens in aquaculture worldwide. It causes a highly contagious disease in salmonids that has a significant economic impact in almost every country where salmonid fish are farmed. For decades IPNV studies have focussed on the molecular characterisation of isolates collected from around the world and the discovery of molecular markers associated with virulence and pathogenicity. The great success of selective breeding for resistance to IPNV has caused special emphasis to be put on the immune response of salmon genetically resistant/susceptible to IPNV. In this work, we review the classification of IPNV, summarise virulence markers and add recent findings about the molecular epidemiology and worldwide distribution of the virus. We also review genetic improvements for IPNV resistance, the kinetics of the immune response to IPNV and the transcriptomic response of salmonids, made possible through the use high-throughput technologies. © 2021 John Wiley & Sons Australia, Ltd